Upstarts : how GenY entrepreneurs are rocking the world of business and 8 ways you can profit from their success. - Fenn, Donna, ....- (New York : McGraw-Hill, 2010)
They're young, they're brash,they're smart-and they're77-million strong.Generation Y is creating startups at anunprecedented rate, and their approach tobusiness is unlike anything you've seen.The generation described by the mediaas spoiled, entitled, even narcissistic, is provingthese notions false every day. Inspiredby the rock-star entrepreneurs of previousgenerations and driven by a burning desireto control their own destinies, GenY is rewritingthe entrepreneurial playbook one coolstartup at a time.Inc.magazine writer Donna Fenn interviewedmore than 150 young CEOs to learnwhat makes them tick. While upstarts aremotivated by similar aspirations of pastgenerations, their way of doing business isradically different-and it's changing the wayeveryone must do business now.Upstartsexaminesand analyzes this entrepreneurialrevolution to reveal eight critical lessons everyentrepreneur and marketer must learn.Fenn describes a generation of entrepreneursthat is highly collaborative and teamoriented.It's quick and alert when it comes tonew technologies. It's hell-bent on changingthe world. And it's totally impatient with outmodedbusiness models.The sooner you adapt to the new way ofbusiness, the greater chance you have togrow and profit in the years ahead.Upstartsprovides key insight into: Building collaborative tribes Deploying technology to yourcompetitive advantage* Disrupting the status quo Deconstructing the GenY market Generating branding buzz Adopting a social mission Inventing the workplace of the future Reinventing your companyMisreading GenY companies could be thebiggest business mistake you ever make. Thisforward-looking book serves both as a headsupto the far-reaching changes coming yourway and as a detailed guide to meeting theresulting challenges.The upstarts are here to stay. Are you?